Dynamic Stability Enhancement of SMIB Power System with PSS-SVC with LQR Optimal Control - K Himaja; T. Anil Kumar; S. Tara Kalyani (Technological Innovation in Engineering Research Vol. 3, 2022)
The dynamic stability analysis of Single Machine Infinite Bus (SMIB) test system with Power System Stabilizer (PSS), Static Var Compensator (SVC) and Linear Quadratic Regulator (LQR) optimal control for a test system under small disturbance presented in this chapter. The test system is derived using Heffron-Phillip’s model. PSS and SVC damping controllers are proposed to enhance the dynamic stability in unique system. The performance of the system is checked with eigenvalue analysis and time response results under nominal load condition. To compare with PSS and SVC, LQR with SVC provides better damping compared to SVC, PSS and without control. The SMIB power system simulated in MATLAB-Simulink environment. The performance of damping controllers such as PSS, SVC with LQR optimal Controller tested on SMIB power system and performance compared.